2020
DOI: 10.1038/s41598-020-63368-y
|View full text |Cite
|
Sign up to set email alerts
|

Altered organization of collagen fibers in the uninvolved human colon mucosa 10 cm and 20 cm away from the malignant tumor

Abstract: Remodelling of collagen fibers has been described during every phase of cancer genesis and progression. Changes in morphology and organization of collagen fibers contribute to the formation of microenvironment that favors cancer progression and development of metastasis. However, there are only few data about remodelling of collagen fibers in healthy looking mucosa distant from the cancer. Using SHG imaging, electron microscopy and specialized softwares (CT-FIRE, CurveAlign and FiberFit), we objectively visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 45 publications
8
41
0
Order By: Relevance
“…Samples that present more organized collagen structures lead to the increment of B values 40, 41 . This trend is also observed in studies, where anisotropy coefficient β is calculated and measured 42 . Angle δ in Equation 2 corresponds to the angle between laser's propagation and fiber's axes.…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Samples that present more organized collagen structures lead to the increment of B values 40, 41 . This trend is also observed in studies, where anisotropy coefficient β is calculated and measured 42 . Angle δ in Equation 2 corresponds to the angle between laser's propagation and fiber's axes.…”
Section: Methodssupporting
confidence: 68%
“…It has to be noted that in the experimental design of the current work, a forward detection scheme was employed for the collection of the SHG images from thin paraffin‐embedded sections. Although SHG anisotropy parameter values depend on the detection geometry, 49 the extracted information could be useful as a novel diagnostic tool for a quick characterization of newly excised thin biopsy samples.. A recent study using PSHG reflection measurements at colon mucosa samples shows that cancer may increase collagen fibrils organization even 20 cm away from cancerous area 42 …”
Section: Discussionmentioning
confidence: 99%
“…Second-harmonic generation (SHG) microscopy has emerged as a powerful method for imaging collagen fibers with submicron resolution in a diverse range of tissues, which is highly selective to the collagen fibril/fiber structure and can visualize collagen fibers several hundred microns deep into the tissue using excitation light at infra-red range (800–1200 nm). SHG imaging on large intestinal tissues was reported by several recent studies in the literature [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. Compared with conventional staining methods on thin tissue slides of ~10 microns thick, we recently reported that SHG microscopy can visualize collagen fibers through the thickness of an intact mouse colon (~200 microns thick) and most of the rectum (300–400 microns) [ 46 ].…”
Section: Microscale Experimental Evidence (Large and Small Intestimentioning
confidence: 99%
“…In addition, malignant tumor is reported to alter the organization of collagen fibers in the colonic mucosa even 10 cm to 20 cm away from its location. This tumor causes an increase in collagen fiber thickness which correlates with the formation of invadopodia, i.e., specialized cell structures that increase the migratory capacity of cancer cells [ 85 ]. In contrast, changes in collagen contents in intestinal layers other than the mucosa are rarely reported.…”
Section: Microscale Experimental Evidence (Large and Small Intestimentioning
confidence: 99%
“…Even with a diverse and small cohort of carcinoma samples, it is not surprising that fiber width is different between these and non-malignant samples as we previously showed that collagen fiber width can predict poor outcome in canine mammary tumor patients, even when used in multivariate analysis taking clinical parameters into account. Increased collagen fiber width in the peritumor stroma in human colonic cancer 95 and in the stroma immediately surrounding neoplastic epithelium of pancreatic ductal adenocarcinoma samples was also recognized to favor cancer progression 96 and increased intratumoral collagen width was a powerful predictor of poor outcome in human gastric cancer 97 . The increased fiber width has been shown to correlate with change in cancer cell shape, formation of invadopodia and increased migration 98 , 99 and has recently been shown to mechanically activate myofibroblasts 100 .…”
Section: Discussionmentioning
confidence: 99%